Strengthening of National Insights Preventing Radicalism Towards a Nation Towards Nationalism in The Global Era (Study Case Student Faculty Medan State University of Social Sciences) - Mufidah, Anisah; Afrillia Surbakti, Fina; Damanik, Denada; Pratiwi, Dina; Mustika, Fanny; Ivanna, Julia (Journal of Community Service For Indonesian Society, 2023)
Outlook nationality is thing that isn't Can released from life every Indonesian citizen . this because outlook nationality is part from understanding citizen . because That importance strengthening and development about outlook nationality for generation ever young experience the changing times worldwide or in the global era. This article or article writer for purpose For know about How strengthening outlook nationality prevent radicalism going to nation aware nationalism in the global era. As for the type research conducted writer that is study qualitative Then use technique author data collection use method observation as well as interview to student Faculty Medan State University of Social Sciences . Based on results study so strengthening outlook nationality among generation young or student in effort maintain republic This from threat radicalism that is can applied through education character through eye lesson or eye Citizenship Education course , p This is because of Citizenship Education hold role important in strengthening implementation insightful education nationality.